Understanding the Passage of the Emmitt till Antilynching Act from the Kingdon’s Multiple Streams or Three Stream Policy Window Model Perspective - Mbah, Ruth Endam; Hultquist, Laura; Repp, Rande (Advances in Social Sciences Research Journal, 2022)
The historical signing into law of the Emmitt Till Antilynching Act in March 2022 ends a long struggle of over a century of almost 200 failed attempts to pass anti-lynching legislation that makes lynching a federal hate crime. For a bill to become law, it must be approved by the House and passed by the Senate in identical form, and be signed by the President. The purpose of this review paper is to understand the policy process leading to the famous signing into law of the Emmitt Till Antilynching Act in March 2022. We use one of the most used models for comprehending policy processes called Kingdon’s Multiple Streams or Three Stream Policy Window Model to evaluate this process. John Kingdon’s model postulates that for a societal issue to pass on as law, it must satisfy three streams, that is (1) Problem Stream, (2) Policy Stream, and (3) Politics Stream. These three streams must come together (policy window) for legislation to be signed into law. However, a policy window could open but if the political climate is not favorable, legislation may not be signed into law at the close of that policy window. It might take several years before another policy window opens again. This was the case of the 200 failed anti-lynching bills from the first anti-lynching bill introduced in 1900 until the historical Emmitt Till Antilynching Act that was approved by the House, passed by Senate, and signed into law by President in 2022.